2020
DOI: 10.48550/arxiv.2008.13325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational bounds to light-matter interactions via local conservation laws

Zeyu Kuang,
Owen D. Miller

Abstract: We develop a computational framework for identifying bounds to light-matter interactions, originating from polarization-current-based formulations of local conservation laws embedded in Maxwell's equations. We propose an iterative method for imposing only the maximally violated constraints, enabling rapid convergence to global bounds. Our framework can identify bounds to the minimum size of any scatterer that encodes a specific linear operator, given only its material properties, as we demonstrate for the opti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…In summary, we have shown that recently developed methods for calculating limits on sesquilinear electromagnetic objectives [42,45,[51][52][53], can be applied to a wide variety of design problems, including spatial multiplexing [22][23][24], metaoptics [92][93][94][95], linear computation [25][26][27] and light extraction [96][97][98][99]. Employing the language of communication theory, this program stands as a significant extension of prior work on channel-based electromagnetic limits [8,30,[55][56][57][58][59][60].…”
Section: Summary Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In summary, we have shown that recently developed methods for calculating limits on sesquilinear electromagnetic objectives [42,45,[51][52][53], can be applied to a wide variety of design problems, including spatial multiplexing [22][23][24], metaoptics [92][93][94][95], linear computation [25][26][27] and light extraction [96][97][98][99]. Employing the language of communication theory, this program stands as a significant extension of prior work on channel-based electromagnetic limits [8,30,[55][56][57][58][59][60].…”
Section: Summary Discussionmentioning
confidence: 92%
“…Archi-tectures possessing impressive field-transformation capabilities have already been demonstrated, from free-space (grating) couplers [33,34] to beam steering [35,36] and polarization control [37,38], suggesting that large-scale optimization methods may allow scattering attributes to be tailored to a far greater degree than what has been seen in past intuition-based designs. Simultaneously, ramifying from the core ideas of Lagrange duality and interpreting physical relations as optimization constraints expounded below [39][40][41][42], a string of recent articles on improved bounds for scattering phenomena (including radiative heat transfer [32], absorbed power [43], scattered power [44], and Purcell enhancement [45]) have shown that, in some cases, only modest improvements over standard designs are even hypothetically attainable [44][45][46][47][48][49][50][51][52][53].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is an emerging interest in identifying fundamental limits to response in such structures [44,64], and the QCMT framework could be ideal for identifying new bounds via the convenient mode/channel structure of the underlying equations. The QCMT framework could be paired with known sum rules on modal densities [65,66], or used in tandem with energy-conservation constraints [67][68][69] to identify the extreme limits of what is possible.…”
Section: Discussionmentioning
confidence: 99%
“…To answer this question, we need to determine a design's suboptimality with respect to some performance metric. Recently, there has been a large amount of work in this area, attempting to find bounds of this form for a variety of metrics, including mode volume [9], free space concentration [10], integral overlap [11,12], among many others [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%